Pointillism in Plant Systems Biology: I. Proteomic Analysis of Plant Exosome-like Particles II. Amyloplast-binding Puroindoline Fusion Proteins for Recombinant Protein Expression. - Greenham, Trevor (Université d'Ottawa / University of Ottawa, 2019)
Expanding upon our understanding of plant defense is critical, particularly with the perilous threats of climate change and overpopulation to our food security, health and well-being. In this study, we focused on plant defense using two distinct approaches. First, we performed a proteomic analysis of plant exosome-like nanoparticles in order to elucidate their defense related protein cargo. Secondly, we used a wheat antimicrobial protein, puroindoline, as a fusion partner for the expression of recombinant proteins in rice endosperm. Plant exosome-like nanoparticles (ELP) were isolated from fresh tomato and subjected to mass spectrometry (MS) analysis. The ELPs were compared to fresh pressed tomato juice, and the proteins that were significantly upregulated in the ELPs were analyzed for their defensive properties. Bioinformatic analysis identified 30 proteins upregulated in the ELPs, with a majority of these being involved in plant defense. Puroindoline is a protein found in soft wheat varieties. A unique feature of this protein is the presence of a tryptophan-rich domain, which causes it to localize and tether onto starch granule surfaces; a property we are seeking to exploit for recombinant protein isolation. We hypothesized that when expressed in a pin-null crop, such as rice, puroindoline along with its fusion partner will localize and adhere to starch granule surfaces. PIN fusions were expressed in rice, and their subcellular localization was determined by immunolocalization. It was observed that PIN localizes to rice starch ii granules in vitro and in planta, and retains its starch granule binding abilities as a fusion partner. To identify other possible starch granule binding fusion partners, an anhydrous cleavage method was developed that can scan dry biological materials for associated proteins, in this case the starch granule surface. Incubation of our cleavage reagent with isolated rice starch granules yielded several cleavage products as determined through SDS-PAGE. These cleavage products were compared with previous proteomic data of trypsin digested rice starch granules.
Keywords: Plant Biotechnology; Exosomes; Anhydrous cleavage; Puroindoline; Starch Granule; Plant Defense; Proteomics; Recombinant Protein; Transgenic; Heptafluorobutyric acid